2008
DOI: 10.1111/j.1742-481x.2008.00542.x
|View full text |Cite
|
Sign up to set email alerts
|

Six‐month mortality risks in long‐term care residents with chronic ulcers

Abstract: Introduction Chronic ulcers are a common problem in long term care. Residents with ongoing ulcers are often frail and at risk for mortality. Aim This study evaluated the relationship between wound characteristics and other health predictors with 6-month mortality in nursing home residents. Subjects Nursing home residents seen by the wound consult service from 1998-2007 with an ongoing chronic ulcer. Methods This was a retrospective cohort study. Data was manually and electronically abstracted for each re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Further, it is known that pressure ulcers are a major predictor of death in patients living at home or in nursing homes. Existing studies have shown that pressure ulcers double the risk of death for these patients during the subsequent year [7,8]. …”
Section: Introductionmentioning
confidence: 99%
“…Further, it is known that pressure ulcers are a major predictor of death in patients living at home or in nursing homes. Existing studies have shown that pressure ulcers double the risk of death for these patients during the subsequent year [7,8]. …”
Section: Introductionmentioning
confidence: 99%
“…19 We recently found that cognitively intact NH residents with cancer reported lower health-related quality of life than that reported by residents without cancer. 15,16 Most people with cancer experience anxiety at some point during the course of diagnosis and treatment and often at crisis points such as the initial diagnosis or discovery of a relapse after treatment. 22 Previous longitudinal studies of older people living in NHs have included depression but not anxiety symptoms.…”
mentioning
confidence: 99%
“…However, one recent study has demonstrated that the summation of all types of ulcers was associated with increased mortality at 6 months with a HR ¼ 1.32 (95% CI 1.07-1.63). 29 Unfortunately, that study did not disclose the proportions of the various wound classes or account for their co-occurrence.…”
Section: Discussionmentioning
confidence: 98%